PERFORMANCE ASSESSMENT OF VILLAGE APPARATUS "WARINGINSARI TIMUR" WHEN WFH USING WEIGHTED PRODUCT AND SIMPLE ADDITIVE WEIGHTING METHODS - Nungsiyati Nungsiyati; Siti Mukodimah; Evi Rahmawati (Jurnal TAM (Technology Acceptance Model), 2021)
One of the ways that the government can improve the quality of village apparatus performance is to conduct a performance assessment. The performance assessment aims to provide morale to village apparatus to continue to improve their performance. The problem that occurs is the number of assessment criteria used in the performance appraisal. The method used in assessing the performance of village apparatus uses the Weighted Product and Simple Additive Weighting methods to provide recommendations for assessing the performance of village apparatus. In accordance with the results of the tests that have been carried out, the calculation results of the preference value of Simple Additive Weighting have a performance that can be said to be better than the Weighted Product because Simple Additive Weighting is able to minimize the preference value on the same alternative. From the results of the comparison between the calculation of Simple Additive Weighting and Weighted Product, the results of testing the application of the Weighted Product (WP) and Simple Additive Weighting (SAW) methods in the decision support system for assessing the performance of village apparatus is that decision support using two methods can produce the best alternative and has accuracy which is high when combined with using a website-based application using criteria that are tailored to the needs of village apparatus, especially during the work period using the current WFH (Work From Home) model. Application Test Results can be used as a basis for structured decision making to support the quality assurance process for Village services in Waringinsari Timur